Evaluasi Kebijakan Ekonomi Lingkungan: Tinjauan Literatur Terhadap Efektivitas Instrumen Ekonomi dalam Pengelolaan Sumber Daya Alam - Primajana, Dewa Jati; Premananda, Wayan Hari (Bumi Lestari, 2025)
This study evaluates the implementation of environmental economic instruments in Indonesia's natural resource management. While progress has been made, several challenges remain in ensuring that these instruments effectively contribute to sustainable development. Key factors influencing the success or failure of implementation include policy communication, the availability of human and financial resources, the commitment of policy implementers, and the complexity of bureaucratic structures. Additionally, the balance between economic growth and environmental preservation remains critical, especially in the post-pandemic economic recovery period. Findings suggest that economic policies focused on recovery may undermine environmental protection measures, thus delaying Indonesia’s greenhouse gas emission reduction targets. Recommendations for improving natural resource management include strengthening cross-sectoral coordination, enhancing community participation, leveraging innovative technologies, and developing more comprehensive strategies. These efforts are necessary to promote both economic growth and environmental sustainability, ensuring long-term prosperity for future generations